PEMIKIRAN NAWAWl AL BANTANI TENTANG MUNAKAHAT DAN RELASI GENDER - Ahmad Sanusi (Al Qalam, 2015)
Nawawi al-Bantani (1230-1316 AH. /1813-1898 AC.) is a Syafi'i scholar from Indonesia who stayed in Mecca and was productive in writing variety of fiqh books. One important topic on his fiqh is about marriage (fiqh al-munakahiit) and women's role. However, many Indonesia feminists is considere his thougt to be gender biased and therefore is considered to irrelevant to contemporary development of fiqh munakahat However, Nawawi 's thought of munakahat is very popular and it is still taught at variety of pesantren as well as madrasah in Indonesia The result of this research shows (1) fiqh Nawawi al -Bantani's thought in munakahat is not far different from other books in Syafi 'i' s school. It is stated on Nawawi's muqadimah book that his work is of several books of mu'tamad Syafi 'i school. (2) Some Nawawi's thought are considered to be gender biased Because, he put women in domestic sphere to serve men, and not to put women in equal and reciprocal gender relation (3) Several Nawawi's thoughts are still rellevant tocontempary development. It is proven on Nawawi's thought of marriage contract, term and harmonious marriage, approval of two parties, marriage age, guardian as term and harmoniousmarriage, witness in marriage, dowry, prohibition in marriage, kafa'ah, right and obligation of marriage couple, divorce and its consequences, idda/waiting period, mut'a and time living idda and reconciliation are incorporates into positive Indonesia Marriage law no. 1 year 1974 and the Compilation Islamic law. But considering to the marriage law as considered discriminatory, it is necessary to the change that law to be more accommodative that supports the concept of the equality of gender relation in a marriage. Keywords: thinking, fiqh, fiqh munakahat, gender, relation gender, women